Evaluation and Comparison of Respiratory Muscular Strength, Functionality, and Pelvic Floor in the Immediate Postpartum of Normal and Cesarean Birth - Carolina Martins da Rosa; Thariny Huesken Dockhorn; Juliana Rezende Cardoso; Soraia Genebra Ibrahim Forgiarini; Luiz Alberto Forgiarini Junior; André Luiz Lisboa Cordeiro (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2023)
Abstract Objective: To evaluate and compare peripheral, pelvic floor, respiratory muscle strength, and functionality in the immediate puerperium of normal delivery and cesarean section. Methods: This is a cross-sectional study that verified respiratory, pelvic floor, peripheral, and functional muscle strength through manovacuometry, pelvic floor functional assessment (PFF), dynamometry, and the Time Up and Go (TUG) test, respectively. The groups were divided according to the type of delivery, into a cesarean section group and a normal parturition group. Results: The sample was composed of 72 postpartum puerperae, 36 of normal parturition, and 36 of cesarean section, evaluated before hospital discharge, mean age ranged from 25.56 ± 6.28 and 28.57 ± 6.47 years in puerperae of normal parturition and cesarean section respectively. Cesarean showed higher pelvic floor strength (PFF) compared to normal parturition (p < 0.002), but puerperae from normal delivery showed better functionality (p < 0.001). As for peripheral muscle strength and respiratory muscle strength, there was no significance when comparing the types of parturirion. Conclusion: There is a reduction in pelvic muscle strength in puerperae of normal delivery and a decrease in functionality in puerperae of cesarean section.